Independent policy strategy as a breakthrough to post-natural disaster recovery in Indonesia (Case Study of Mount Sinabung Eruption, Karo District, North Sumatra) - Harmensyah Harmensyah (Enrichment : Journal of Management, 2023)
Indonesia is prone to earthquakes, tsunamis, volcanic eruptions, hydro-meteorological disasters, floods, flash floods, landslides, droughts, forests, and land fires, impacting people's lives and livelihoods. This scientific paper is intended for all interested parties in making quick and appropriate choices, especially post-disaster recovery, rehabilitation, and reconstruction. This study uses a case study approach to describe the research results and find out how the Strategy for Implementing the Independent Relocation Policy in areas affected by the Mount Sinabung Eruption in North Sumatra Province is appropriate to become a future recovery policy. The locus chosen as the case study was in Karo District, North Sumatra, where the research was conducted for residents affected by the Sinabung volcano eruption, but later the results can be used for all types of disasters. Mandiri Relocation is an independent relocation scheme in Indonesia that can quickly solve relocation problems faced by disaster-affected communities. It is a breakthrough and answer that has never been implemented as a relocation policy in Indonesia or even the world. If sufficient land is available, the local Government can relocate the community. However, if the local Government needs help providing relocation land, new problems will arise during the displaced community, such as uncertain life, health declines, education, and socio-economic conditions. If a solution is not found, it will be hazardous for their future.